Challenges and prospects of records maintenance in public departments: The case of the Midlands Province, Zimbabwe - Katekwe, Petronella; Mutsagondo, Samson (SAGE Publications Ltd, 2021)
Records maintenance is a critical aspect of records management, which guarantees the availability of records now and into the future. Unfortunately, a plethora of challenges face both creating departments and the secondary depository facility, a situation which threatens the records lifecycle. This work looks at records maintenance challenges faced by government ministries and the Gweru Records Centre in the Midlands Province of Zimbabwe. Using questionnaires and document reviews, data were collected from records and information management officers in 25 government ministries in the province as well as from staff of Gweru Records Centre. Due to lack of records management knowledge and financial challenges, many government ministries are not transferring semi-current records when transfer is due. At the same time, Gweru Records Centre is unable to accession large volumes of records from creating departments due to space, logistical and operational challenges. However, a number of activities are being carried out by the Centre to redress the situation. The study recommends provision of financial resources for records management and staff development programmes to inculcate behavioural change among records staff and management in government ministries, as well as the establishment of a large purpose-built records centre in the Midlands Province.